Effects of flooring types on teat end bacteria counts, milk quality, hygiene and behaviour of dairy cows housed in tie-stall closed barn: Effects of Flooring Types on Teat End Bacteria Counts, Milk Quality, Hygiene and Behaviour of Dairy Cows Housed in Tie-stall Closed Barn - Aydın, Recep; Diler, Abdülkerim; Ozdemir, Veysel Fatih; Yanar, Mete; Koçyiğit, Rıdvan (Veterinaria Italiana, 2023)
This study aimed to investigate environmental mastitis causing bacteria counts in the teat end, somatic cell counts (SCC) of milk samples, cleanliness scores and behavior of cows kept on concrete and rubber mat floorings. For this purpose, 19 Holstein-Friesian dairy cows were allocated into concrete and rubber mat groups. Swab samples were taken from the teat ends to determine the bacterial counts causing environmental mastitis. Milk samples were collected from a composite of all four quarters to determine the SCC. Instantaneous sampling method was utilized to observe the behavioral activities of cows. Cows were visually evaluated to determine the udder cleanliness score. Independent samples t-test was utilized in the statistical analysis of the obtained data. Coliform (P<0.05), Escherichia coli, and Klebsiella spp. (P<0.01) counts of the swab samples taken from the cows housed on concrete flooring were significantly higher than rubber mat group. However, no statistically significant differences were found between groups in terms of total bacteria, Streptococcus spp., and Enterobacteriaceae counts. The SCC on samples taken from cows kept on concrete surface were significantly higher (P<0,05) than that of animals housed on rubber mat. Furthermore, cows in the rubber mat group were determined to be significantly cleaner (P<0.05) than those in concrete group. It was also determined that the cows housed on rubber mat spent significantly longer time for lying behavior (P<0.05), which is a significant indicator of animal comfort. The time spent for standing without eating was considerably higher (P<0.01) in concrete group. In addition, the times spent for eating was significantly lower (P<0.01) in the concrete group. It was concluded that, using rubber mat instead of concrete for flooring in tie-stall barns decreases the contamination of environmental mastitis pathogens, increases milk quality and cow cleanliness score as well as animal comfort and welfare.